Human impact changes hydrological connectivity in a Patagonian fluvial basin - Scordo, Facundo (2023)
Study region: The Cronómetro Lake basin situated east of the Andes in Argentina's Patagonian Andean pre-range environment. Study focus: We analyzed the interannual fluctuation in the surface area of Cronómetro Lake (January 2000 to January 2021). We also studied the periods of humidity and drought and the anthropogenic activities in the lake basin to understand their impact on water availability within the basin. New hydrological insights for the region: The area of Cronómetro Lake decreased by 34% in the last ten years. The lake's area reduction started in 2012, which coincides with the construction of fourteen channels perpendicular to one of its main tributaries (the SN1 Stream). The channelization of the SN1 Stream in its upper basin prevents its water from reaching the Cronómetro Lake. From 2012–2021, we have not observed a decrease in local rainfall or an increase in periods of drought. Therefore, we suggest the channelization of the SN1 Stream is the cause of the lake shrinkage. The reduction of the lake's surface generated the disconnection of the lake from its outflow, which dried. Currently, the Cronómetro Lake basin has become endorheic. The reduction in water availability in the Cronómetro Lake basin causes loss of aquatic and terrestrial ecosystem services, with negative implications for local economic activities.